Effect of garlic (Allium sativum L.) essential oils on Oncorhynchus mykiss fillets during storage - Karaton Kuzgun, Nermin (Progress in Nutrition, 2019)
Suitable pH, very amounts of rich nutrients and with high Aw aquatic products are often perishable. This situation, it has become an important restriction in aquatic food product industry. Aimed to this study, reported resulting effect of garlic essential oils in terms of microbiological changes, chemical changes and organoleptic changes on Oncorhynchus mykiss fillets during storage at 2±2°C for 15 days. In the Quality loss of fillets were evaluated by pH, total volatile basis nitrogen (TVB-N), Thiobarbituric acid (TBA), aerobe bacteria (AB), psychrophilic bacteria (PB), lactic acid bacteria(LAB), yeast-mold and organoleptic characteristics. Findings showed that Trout fillets non treatment with Garlic essential oils exhibited significant quality decline after 6 days of storage. Shelf life of products throughout, in terms of AB, PB, LAB and yeast-mold count was determined that the products with the least growth were in the groups treated with 4% garlic oil. Fillets apply with garlic essential oil (especially 4%) was more effective in controlling quality changes in fillets shelf life with lower TVB-N, TBA and organoleptic scores.